2021
DOI: 10.3390/cancers13102504
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Penetrating CEBPB and CEBPD Leucine Zipper Decoys as Broadly Acting Anti-Cancer Agents

Abstract: Transcription factors are key players underlying cancer formation, growth, survival, metastasis and treatment resistance, yet few drugs exist to directly target them. Here, we characterized the in vitro and in vivo anti-cancer efficacy of novel synthetic cell-penetrating peptides (Bpep and Dpep) designed to interfere with the formation of active leucine-zipper-based dimers by CEBPB and CEBPD, transcription factors implicated in multiple malignancies. Both peptides similarly promoted apoptosis of multiple tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 64 publications
(59 reference statements)
1
44
0
Order By: Relevance
“…We included several CPPs that have been previously reported to augment peptide vaccines: penetratin (pAntp) ( 36 , 39 ), HIV transactivator of transcription (Tat) ( 38 , 44 ), Arg 8 ( 45 ), and MPG ( 46 ). Additionally, this series included CPPs that, to our knowledge, have never been tested for vaccine antigen delivery: Bpep ( 29 ), Diatos peptide vector 6 (DPV6) ( 47 ), vascular endothelial cadherin-derived peptide (pVEC) ( 48 ), and Transportan 10 (TP10) ( 49 ). Each CPP was conjugated via copper(I)-catalyzed click chemistry to the C terminus of an 18-mer-long peptide (gp100 20–38 , hereafter gp100) encompassing the H-2D b –restricted epitope EGPRNQDWL (gp100 25–33 ) of the melanoma tumor-associated antigen ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included several CPPs that have been previously reported to augment peptide vaccines: penetratin (pAntp) ( 36 , 39 ), HIV transactivator of transcription (Tat) ( 38 , 44 ), Arg 8 ( 45 ), and MPG ( 46 ). Additionally, this series included CPPs that, to our knowledge, have never been tested for vaccine antigen delivery: Bpep ( 29 ), Diatos peptide vector 6 (DPV6) ( 47 ), vascular endothelial cadherin-derived peptide (pVEC) ( 48 ), and Transportan 10 (TP10) ( 49 ). Each CPP was conjugated via copper(I)-catalyzed click chemistry to the C terminus of an 18-mer-long peptide (gp100 20–38 , hereafter gp100) encompassing the H-2D b –restricted epitope EGPRNQDWL (gp100 25–33 ) of the melanoma tumor-associated antigen ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CPPs are linear peptides ∼5- to 40-amino acid residues in length that are generally comprised of cationic or amphipathic membrane-interactive sequences. CPPs can be natural sequences derived from proteins (e.g., penetratin from the Antennapedia homeodomain of Drosophila ) ( 28 ), designed de novo sequences (e.g., Arg 8 ) ( 26 , 27 ), or hybrid natural/synthetic sequences (e.g., Bpep) ( 29 ). They can promote endocytosis and, in some cases, direct cytosolic delivery of linked cargos ranging from small molecules to oligonucleotides, and proteins via interactions with various components of the cell surface, including glycans, endocytic receptors, and the plasma membrane itself ( 30 32 ).…”
mentioning
confidence: 99%
“…In the present work, their binding (at the −1076 to −932 region of the SPINK5 promoter) and negative relation has been verified using ChIP, dual-luciferase report assay, correlation analysis as well as western blot assays. CEBPB has been revealed to promote survival, growth, metastasis and treatment resistance of a broad spectrum of cancer cell types [22]. Similarly, CEBPG has been established to activate the PI3K/ protein kinase B signaling in esophageal squamous cell carcinoma cells by directly binding to promoters of genes in this pathway, including CCND1, MYC and CDK2 [23].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that CP-DN-ATF5 can also interfere with endogenous CCAAT enhancer-binding protein beta (CEBPB) and delta (CEBPD) activities, whose inhibition promotes tumor cell death [85]. Consequently, Bpep and Dpep were designed to interfere with ATF5, CEBPB, and CEBPD and promote cell death by down-regulating the anti-apoptotic protein survivin and up-regulating proapoptotic BCL2modifying factor (BMF) [86]. CP-DN-ATF5 has also been shown to induce apoptosis by down-regulating survivin [87].…”
Section: Atf5 In Cancer Therapymentioning
confidence: 99%